The Influence of Organizational Culture and Work Discipline on Employee Performance at PT. PLN (Persero) Masamba Customer Service Unit - Nanna, Nanna; Saharuddin, Saharuddin; Khaddapi, Muammar (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The results of this study aim to determine and explain the influence of Organizational Culture and Work Discipline on Employee Performance at PT. PLN (Persero) Masamba Customer Service Unit, this type of research uses a quantitative approach. The sample of this study is 40 employees, the simultaneous results of Organizational Culture and Work Discipline have a significant influence on Employee Performance with the value of the t test results of Organizational Culture obtained t value greater than t table (0.317> Î± 0.05) and Motivation in get a t count value of 0.000 < Î± 0.05.